Burnout Syndrome and its associated factors among anesthesia technicians in a Teaching Hospital in the central region of Tunisia - Athimni, Z.; Chouchen, A.; Kalboussi, H.; Nsiri, L.; Ferhi, F.; Aloui, A.; Gaddour, A.; Bouhoula, M.; Maoua, M.; Brahem, A.; Maalel, O.; Chatti, S.; et al. (European psychiatry, 2023)
IntroductionBurnout (BO) is a syndrome combining psychological and somatic symptoms caused by exposure to several years of chronic stress at work. Far from being a theoretical problem, it is a real social problem that has become globalized as societies change. Anesthesiology is among the most stressful medical disciplines which expose to BO in Tunisia and around the world.ObjectivesIdentify associated factors to BO among anesthesia technicians.MethodsWe conducted a cross-sectional study during two months, from October 1st, 2015 to December 31th, 2015, among anesthesia technicians affected in the different operating rooms of the Farhat Hached teaching Hospital in Sousse. Data collection was based on a self-administered questionnaire with validated tools assessing BO (Maslach Burnout Inventory) and stress (Siegrist and Karasek)..ResultsForty-six senior anaesthesia technicians was included in the study. The mean age of our population was 43.76 ±7.74 years with a female predominance (89.1%). According to the Karasek model, 59% of the workers were in job strain, and according to the Siegrist model 23.9% of the participants had an imbalance between high effort and low reward. The BO rate among anaesthesia technicians at the Farhat Hached University Hospital was 39.1%. The results showed a statistically significant association between working at the gynaecology-obstetrics department (p=0.001), the seniority in the department superior or equal to 20 years (p=0.006), the absence of break time at work (p=0.003) and the risk of the occurrence of BO. Furthermore, the last 2 consecutive day rest dates back to more than 15 days (p=0.001), the number of free weekends during the last 3 months less than four (p=0.044) were also significant associated to BO.ConclusionsOur study confirms that BO is a tangible reality in our country especially among anesthesia technicians, so it must be addressed by adopting effective preventive strategies.Disclosure of InterestNone Declared